PENENTUAN BESARNYA ANUITAS HIDUP DENGAN MENGGUNAKAN NILAI ASUMSI PADA DISTRIBUSI SISA USIA - Farah Kristiani (Jurnal Matematika Sains dan Teknologi, 2010)
There are two kinds of annuity, annuity certain and life annuity. Annuity certain does not depend on life probability, for example, mortgage. Life annuity depends on time until death and life probability, for example, pension payment from insurance company. The objective of this paper is to discuss further about life annuity and the relationship with life probability that is influences by time until death and the assumption of interest which is used. Time until death (T) is a random variable, because it is unpredictable. To determine the value of distribution, assumption values on tqx will be used. These values are generated by T simulation which depends on Uniform distribution (0,1) random values. A few cases of determining life annuity using tpx distribution values by T simulation will be discussed.